THE INFLUENCE OF TRANSFORMATIONAL AND TRANSACTIONAL LEADERSHIP STYLE TOWARDS EMPLOYEE COMMITMENT IN MALAYSIA ROYAL CUSTOMS ORGANIZATION - Isa, Khairunesa (Journal of Techno-Social, 2013)
The purpose of this study is to investigate the influence of transformational and transactional leadership styles towards employee commitment in Malaysia Royal Customs Organization. All the dimension of transformational and transactional leadership style has been studied to determine the influence towards employee commitment. A total of 100 subordinates were chosen by simple random sampling and participated in this study. Set of questionnaire has been used as a instrument for the purpose of data collection. The Multifactor Leadership Questionnaire (MLQ) was used to measure the leadership style of the directors while An Organizational Commitment Questionnaire (OCQ) was used to measure the level of commitment of the employee. Data collected were further analyzed using the descriptive statistics and the inferential statistics. The findings shows that there is a significant relationship between transformational and transactional leadership styles of leader and the level of employee commitment. Based on each dimensions, the result shows that dimension of individualized consideration have a high positive significant compared to the other dimension like charismatic, intellectual stimulation, contingent reward and management-by-exception with the level of employee commitment and 60% of employee commitment are influenced by transformational leadership style.